Role of the PADI family in inflammatory autoimmune diseases and cancers: A systematic review - Zhu, Changhui; Liu, Chunyan; Chai, Zhengbin (Frontiers in Immunology, 2023)
The peptidyl arginine deiminase (PADI) family is a calcium ion-dependent group of isozymes with sequence similarity that catalyse the citrullination of proteins. Histones can serve as the target substrate of PADI family isozymes, which results in the involvement of the PADI family in NETosis and the secretion of inflammatory cytokines. Thus, the PADI family is associated with the development of inflammatory autoimmune diseases, cancer, reproductive development and other related diseases. In this review, we systematically discussed the role of the PADI family in the pathogenesis of various diseases based on studies from the past decade to provide a reference for future research.